Analysis of premise infrared heating and ventilation with an exhaust outlet and flat decking air flow - Nadiia Spodyniuk; Orest Voznyak; Olena Savchenko; Oleksandr Dovbush; Mariana Kasynets; Oleksandra Datsko (Diagnostyka, 2022)
The article is devoted to solving of urgent problem to analyse energy saving effect from radiant heating and ventilation of premise with exhaust outlet and flat decking air jet. The aim of the work is analysis of energy efficiency of radiant heating systems using infrared heaters and ventilation of the premise due to the effect of a flat decking air jet on the surface of the heater; determination the amount of heat received both by flat decking air jet from the infrared heater when laying on its flat surface and amount of heat from the exhaust air entering the recuperator. Use of the infrared heaters in combination with an air distribution of the ventilation system with the flat decking air jets is effective, as it allows to achieve savings in heat load of the ventilation system in the range of 11% - 19%. The amount of heat recovery of the exhaust air removed by the exhaust outlet is 30 - 40 W that equals 15% - 20%. Saving the heat load of the ventilation system allows reducing the actual initial temperature of the tidal flat decking air jet and achieving a total saving of thermal energy of 24% - 34%.